The history of the formation of the institute of surrogacy: socio-legal context - Seidinova, M.A. (Bulletin of the Karaganda University “Law Series”, 2022)
The birth of a child is impossible or dangerous for the life and health of the mother due to physiological deficiencies, biological incompatibility of spouses, contraindications for pregnancy, a number of hereditary diseases, etc. Moreover, the causes of infertility are equally distributed between both sexes. All this leads to the disintegration of the family, the dissolution of marriage, as a result, to the deterioration of the demographic situation, and, consequently, to the violation of the human right to health, medical confidentiality and a prosperous life. One of the ways out in this situation is seen in the application of methods of artificial insemination, one of which is surrogate motherhood, and the improvement of legislative regulation of the most important relations that directly affect demographic processes. The author of the article proposes to consider the stages of the formation of the institution of surrogate motherhood, starting from the first mentions in social history and ending with the history of the emergence of assisted reproductive technologies in modern Kazakhstan. Particular attention is paid to the legislative regulation of assisted reproductive technologies in the USA, Great Britain, the USSR, the Russian Federation and in modern Kazakhstan. Conclusions are drawn about the need to improve national legislation in the field of protecting the rights of a surrogate mother and child, the development and introduction of a separate law on surrogate motherhood.